Performance investigation of LabPET II detector technology in an MRI-like environment. (24th January 2020) - Moghadam, Narjes; Arpin, Louis; Espagnet, Romain; Bouchard, Jonathan; Viscogliosi, Nicolas; Lecomte, Roger; Fontaine, Réjean
Abstract: The EMI-compatibility of the LabPET II detection module (DM) to develop a high-resolution simultaneous PET/MRI system is investigated. The experimental set-up evaluates the performance of two LabPET II DMs in close proximity to RF coils excited at three different frequencies mimicking the electromagnetic environments of 3 T, 7 T, and 9.4 T MRI scanners. A gradient coil, with switching frequency from 10 kHz to 100 kHz, also surrounds one of the DMs to investigate the effects of the gradient field on the individual detector performance, such as the baseline of the DC-voltage and noise level along with both the energy and coincidence time resolutions. Measurements demonstrate a position shift of the energy photopeaks (⩽9%) and a slight deterioration of the energy and coincidence time resolutions in the presence of electromagnetic interferences from the gradient and RF coils. The electromagnetic interferences cause an average degradation of up to ~50% of the energy resolution (in time-over-threshold spectra) and up to 18% of the timing resolution. Based on these results, a modified version of the DM, including a composite shielding as well as an improved heat pipe-based cooling mechanism, capable of stabilizing the temperature of the DM at ~40 °C, is proposed and investigated. This shielded version shows no evidence of performance degradation inside an MRI-like environment. The experimental results demonstrate that a properly shielded version of the LabPET II DM is a viable candidate for an MR-compatible PET scanner.